Etude de la Variabilité Morphologique de Saba Senegalensis (A. DC.) Pichon en Casamance (Sénégal) - Diouf, Paul; Diedhiou, Siré; Goudiaby, Arfang Ousmane Kémo; Ndoye, Ibrahima; Koita, Bothié (European Scientific Journal, ESJ, 2019)
This study was carried out to better understand the distribution of Saba senegalensis, through an analysis of its morphological variability in different areas of production in Casamance. Leaf and fruit samples were taken from 150 individuals across six (06) sites with high yield. Thirteen (13) morphological descriptors were used. Diembéring, Nyassia and Badiatte individual have a more important foliar development. It is defined by longer leaves (13.69 cm) and longer petioles (1.36 cm) in Diembering and broad leaves (6.26 cm) with short petioles (1.08 cm) inNyassia. InThionk Essyl, SaréBocar and Saré Sara, S. senegalensis individuals are characterized by smaller leaves with 5.77 cm on average. For morphological descriptors related to fruits and seeds, Nyassia and Thionk Essyl show better fruit development. From the results, it appears that the variability of the morphological descriptors studied follows the geographical origin but for some descriptors related to the leaves, their variability is also linked to the genome. Cette étude contribue à une meilleure connaissance de l’espèce Saba senegalensis, à travers une analyse de sa variabilité morphologique selon les zones de production en Casamance. Elle est réalisée dans six (06) sites à fort potentiel de production où des prélèvements de feuilles et de fruits ont été effectués sur 150 individus. Treize (13) descripteurs morphologiques ont été retenus. Les populations de Diembéring et de Nyassia présentent un développent foliaire plus important. Il est défini par des feuilles (13,69 cm) et des pétioles (1,36 cm) plus longs à Diembéring, et des feuilles relativement larges (6,26cm) à Nyassia. Au niveau des sites de Thionk Essyl, Saré Bocar et Saré Sara, l’espèce Saba sengalensis est caractérisée par des feuilles moins larges, avec une moyenne de 5,77 cm. Pour les descripteurs morphologiques relatifs aux fruits et graines, Nyassia et Thionk Essyl présentent un meilleur développement. Il ressort des analyses que, la variabilité des descripteurs morphologiques étudiées suit l’origine géographique mais pour certains descripteurs relatifs aux feuilles, leur variabilité serait liée aussi au génome.